57 Physical Activity Improvement in Elderly Hospitalised Patients at the Royal London: Exercise as Part of A Multimodal Intervention. (16th March 2021) - Sayer, K; Whiteaway, K; Dawson, J O; Simpson, J; Chu, W
Abstract: Introduction: Approximately 65% of elderly patients admitted to hospital experience some level of deconditioning during their stay. This can lead to longer length of stays, premature admissions to care homes and loss of function whilst in hospital (British Geriatrics Society). There is evidence that exercise can be safe and effective in reversing functional decline in this population. However, there is limited evidence into the effectiveness and feasibility of running a multi modal exercise intervention (eg. Dance and Exercise) on a busy elderly care ward in the UK. Method: An 8-week inpatient programme consisting of a 60-minute exercise classes once a week and/or 60-minute dance class once a week started on the Older Person's Wards at the Royal London. Primary outcome measures included: 5 x Sit To Stands (5xSTS) and Falls Efficacy Scale International (FES-I). Secondary measures; Rockwood score, Barthel Index, Elderly Mobility Score (EMS), Mood, 4AT and handgrip strength. Patient satisfaction scores were also recorded. Results: 23 patients were included in the analysis, 3 patients attended the dance class, 14 attended the exercise class and 5 attended both. In total 37 sessions were completed. The average score for all outcome measures improved except one after 8 weeks. The 5xSTS times improved by an average of 7.7 seconds and the FES-I score dropped by 3.9. The Barthel score increased by 5 points. Handgrip strength increased by 2.3 kg and 57% improved on their EMS. Mood improved from 5.4/10 to 6.0/10 and 4AT from 2.7 to 1.7. Overall, 70% of participants reported enjoying the classes and 90% said they would re-attend. Conclusion: A multifactorial intervention including seated dance and exercise sessions showed significant improvements in mobility, fear of falling, cognition and functional tasks. Further work will look into the impact on length of stay and readmissions inpatient to hospital.